Tarbi (JSTOR)
Tarbiz is the only Hebrew academic journal devoted to the entire range of Jewish studies. Appearing quarterly, Tarbiz is the principal forum for the expression of the most important developments in contemporary Jewish studies, and its contributors include the leading scholars in the various fields of Jewish studies in Israel and worldwide, as well as young scholars who are beginning to make their mark.
Keywords: Jewish Studies